2019
DOI: 10.1007/s00125-019-4813-5
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal rhythms in the white adipose tissue transcriptome are disturbed in obese individuals with type 2 diabetes compared with lean control individuals

Abstract: Aims/hypothesis Animal studies have indicated that disturbed diurnal rhythms of clock gene expression in adipose tissue can induce obesity and type 2 diabetes. The importance of the circadian timing system for energy metabolism is well established, but little is known about the diurnal regulation of (clock) gene expression in obese individuals with type 2 diabetes. In this study we aimed to identify key disturbances in the diurnal rhythms of the white adipose tissue transcriptome in obese individuals with type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 52 publications
6
63
0
Order By: Relevance
“…This suggests that misalignment of sleep/wake and feeding/fasting cycles increases the risk of obesity in humans. This could also indicate that metabolic homeostasis influences circadian phase of entrainment, in line with the observation that obesity in high-fat diet (HFD)-fed mice causes disruption of circadian rhythms (Kohsaka et al 2007;Hatori et al 2012) and as also indirectly supported by clinical studies of subjects with metabolic disease such as obesity and type 2 diabetes (Otway et al 2011;Stenvers et al 2019).…”
Section: Feeding As a Signal Of Entrainmentsupporting
confidence: 55%
“…This suggests that misalignment of sleep/wake and feeding/fasting cycles increases the risk of obesity in humans. This could also indicate that metabolic homeostasis influences circadian phase of entrainment, in line with the observation that obesity in high-fat diet (HFD)-fed mice causes disruption of circadian rhythms (Kohsaka et al 2007;Hatori et al 2012) and as also indirectly supported by clinical studies of subjects with metabolic disease such as obesity and type 2 diabetes (Otway et al 2011;Stenvers et al 2019).…”
Section: Feeding As a Signal Of Entrainmentsupporting
confidence: 55%
“…Development of T2DM is associated with dysfunctional adipose tissue phenotype, characterized by increased adipocyte size and a pro-inflammatory response. Increasing evidence shows that disruption of circadian rhythms contributes to disease progression, and it was recently found that daily rhythms in the white adipose tissue transcriptome are disturbed in individuals with T2DM compared with lean individuals [14]. In this study we have used the Psammomys obesus sand rat, a unique animal model that mimics T2DM development in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Shift work has been shown to have significant negative health impacts, with numerous studies reporting an association of shift work with elevated risks for overweight, metabolic syndrome and T2DM [8][9][10][11]. Increasing evidence shows that disruption of circadian rhythms increases the risk of many chronic diseases including T2DM [12,13] and diurnal rhythms in the white adipose tissue transcriptome are disturbed in obese individuals with T2DM [14]. Animal models of chronodisruption that include scheduled food access, high fat diet, mistimed activity, sleep disruption and light exposure all show significant impacts on the development of obesity, metabolic syndrome, impaired glucose metabolism and hyperglycemia [6].…”
Section: Introductionmentioning
confidence: 99%
“…Given the close linkage of obesity, especially central (abdominal) as a key component of the Metabolic Syndrome, obesity plays an important role in risk of T2DM and insulin sensitivity as well as CVD [39]. A role for circadian rhythms, including the circadian clock within the adipocytes, in the development of obesity was described [17,[71][72][73]. As noted earlier, there is also a close relationship with obesity in terms of risk for obstructive sleep apnoea, a key comorbidity.…”
Section: Obesitymentioning
confidence: 93%
“…Herein we discuss research findings relating to the proposed Circadian Syndrome risk components and comorbidities (Table 2). Hypertension Lack of nocturnal decline in blood pressure [30,62] High blood pressure [22] Lipids Disrupted lipid homeostasis [69,70] Obesity Disrupted diurnal rhythms in the white adipose tissue transcriptome [73] Obesity [22] Blood glucose levels Disrupted daily rhythms in blood glucose levels and glucose intolerance [17,21,75] Disrupted daily rhythms in blood glucose levels and glucose intolerance [22] Fatty liver Disrupted triglyceride accumulation, inflammation, oxidative stress and mitochondrial dysfunction [29] Depression Circadian disruption increases the incidences of depression [86,87] Circadian disruption increases the incidences of depression [22,83,84,[105][106][107][108][109][110] Sleep disturbances Circadian disturbances result in sleep loss and mistimed sleep [56,97] Proposing a Circadian Syndrome: Cardiovascular-related components Circadian oscillations have been reported for both physiological CVD regulation including heart rate and blood pressure [57], for cardiac disorders including arrythmias [58,59], and there is circadian variation in frequency of onset of myocardial infarction and sudden cardiac death [19,60].…”
Section: Circadian Disruption and Associations With Risk Factorsmentioning
confidence: 99%